2D dilaton-gravity, deformations of the minimal string, and matrix models. (29th September 2021) - Turiaci, Gustavo J; Usatyuk, Mykhaylo; Weng, Wayne W
Abstract: A large class of two-dimensional dilaton-gravity theories in asymptotically AdS2 spacetimes are holographically dual to a matrix integral, interpreted as an ensemble average over Hamiltonians. Viewing these theories as Jackiw–Teitelboim gravity with a gas of defects, we extend this duality to a broader class of dilaton potentials compared to previous work by including conical defects with small deficit angles. In order to do this we show that these theories are equal to the large p limit of a natural deformation of the (2, p ) minimal string theory.